Emotion Analysis of Arabic Tweets: Language Models and Available Resources - Alqahtani, Ghadah; Alothaim, Abdulrahman (Frontiers in Artificial Intelligence, 2022)
One of the most popular social media platforms is Twitter. Emotion analysis and classification from tweets has become a significant research topic recently. The Arabic language faces challenges for emotion classification on Twitter, requiring more preprocessing than other languages. This article provides a practical overview and detailed description of the material that can help in developing an Arabic language model for the emotion classification of Arabic tweets. The emotion classification of Arabic tweets using NLP, overall current practical practices, and available resources are highlighted to provide a guideline and overview sight to facilitate future work. Finally, the article presents some challenges and issues that can be future research directions.